Existing and Resisting: The Pedagogical Realities of Black, Critical Men and Women Faculty. (28th July 2020) - Haynes, Chayla; Taylor, Leonard; Mobley, Steve D.; Haywood, Jasmine
ABSTRACT: The existing discourse highlighting Black faculty experiences in the classroom are largely hidden among studies that center the experiences of Faculty of Color who teach courses about race, gender, and/or diversity, regardless of their faculty status. And, even fewer of those studies unpack how their pedagogical approaches further complicate the experiences of Black faculty, especially Black faculty without tenure. The authors, who are Black hetero women and Black queer men, used embodied text as a framework to explore their teaching experiences as faculty and critical pedagogues. Where embodied text establishes the body as a site for learning and knowledge, critical pedagogy asserts that neither the classroom nor the knowledge constructed within that space are apolitical. The study findings illuminated how Black faculty bodies were scrutinized and ultimately showed that Black hetero women and Black queer men who were critical pedagogues embodied a resistance text that when read, oftentimes created intertextual pedagogical situations that invalidated their humanity. This research expands the scholarship on embodied text and critical pedagogy by examining the teaching experiences of Black faculty who not only centered critiques of power and privilege in non-diversity courses, but whose bodies were also disruptive in White, hetero, cis-patriarchal academic spaces.